Nanoscale Imaging and Spectroscopy of Plasmonic Modes with the PTIR Technique. Issue 8 (2nd May 2014) - Katzenmeyer, Aaron M.; Chae, Jungseok; Kasica, Richard; Holland, Glenn; Lahiri, Basudev; Centrone, Andrea
<x xml:space="preserve">Abstract</x> The photothermal induced resonance (PTIR) method measures the near‐field absorption in gold plasmonic structures. PTIR absorption images show the interference between the bright and dark modes of asymmetric split ring resonators (ASRRs). The plasmonic absorption spectra of the ASRRs individual arcs are obtained locally, confirming the collective nature of the plasmonic excitation. Scale bars are 500 nm. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>